Iterative algorithm for locating nodes in WSN based on modifying average hopping distances - LIN Jin-zhao1; CHEN Xiao-bing1; LIU Hai-bo1 (Tongxin xuebao)
Three approaches were put forward to improve the poor locating performance of DV-Hop algorithm which is one of the range-free algorithms in wireless sensor network （WSN） with a dynamic topology. Firstly, the average one-hop distance among beacon nodes was refined by means of least squares method （LSM）. Secondly, the average one-hop dis-tance used by each locating node for estimating itself location was modified through weighting the N received average one-hop distances from beacon nodes. Finally, the iterative numerical method with the initial values of estimated node locations was presented by setting proper threshold. The procedure of the iterative locating algorithm based on modifying average hopping distances and the simulation results were also shown. It can be concluded that the improved algorithm has obviously better locating performance in locating precision and precision stability at the cost of increasing appropriate communication and computation overhead, and is a more feasible locating scheme in WSN with both random distributing nodes and dynamic topology.